Factors Influencing The Impulsive Buying Behavior of UINSU Students in Online Stores from an Islamic Economic Perspective, With Rational Choice as an Intervening Variable - Muhammad Sholeh Khan; Syahbudi, Muhammad; Aisyah, Siti (Jurnal Manajemen Bisnis, 2024)
Impulse buying behaviour is a habit that causes problems that must be controlled among students as generation Z perpetrators.  must be controlled among students as generation Z as the culprit. Therefore, it is necessary to control the importance of consumer psychology, utilitarian value, and rational choice. The purpose of this article is to determine the direct and indirect effects of consumer psychological variables, utilitarian value on impulse buying behaviour with rational choice as an intervening variable. This article uses a quantitative approach method. The types of data used are primary data, namely questionnaires and secondary data, namely supporting data from online media and supporting institutions. The data analysis technique used is path analysis (path) intervening. The findings reveal that consumer psychology has a significant direct impact on impulse buying behavior, whereas its indirect effect through rational choice is not significant. Similarly, while utilitarian value directly influences impulse buying behavior, its indirect effect through rational choice is not significant.